Optical simulations and optimization of highly sensitive biosensor for cancer cell detection - Mouncharih, Abdelkarim El; Takassa, Rabi; Farkad, Omar; Tchenka, Abdelaziz; Ibnouelghazi, El Alami; Abouelaoualim, Driss (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
In this work, using the two-dimensional finite difference time domain method, we are theoretically studying the optical properties of a two-dimensional photonic crystal biosensor based on silicon rods arranged as a square structure in an air bottom with two waveguides and a nanocavity. For this purpose, six different cells are infiltrated into the point defect. These six cells are Jurkat, HeLa, PC-12, MDA-MB-231, MCF-7, and basal cells. As a result, we have successfully detected cancer and benign cases of these cells through resonance peaks in the transmission spectrum. We evaluated the sensitivity, quality factor, detection limit, and figure of merit at different values for sensing region radius for optimization purposes. We report that we observed the maximum sensitivity of 1350 nm/RIU at 0.15 μm for the basal cell. Finally, the proposed biosensor can be a miniaturized structure with extreme sensitivity in cancer cell detection models.
Optica Applicata, Vol. 53, 2023, nr 3, s. 407-418
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; refractive index sensor; sensitivity; cancer cells; photonic crystal; finite difference time domain (FDTD)